"Little Dark Age": Nostalgia and Reactionary Nationalism Through Audiovisual Memes on YouTube - Jaspe Nieto, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research explores the ideological and communicative function of "Little Dark Age" (LDA) memes on YouTube, focusing on their use of nostalgia, nationalism, and historical distortions. It employs a qualitative content analysis using the VVVA framework, studying memes from four countries: the United Kingdom, Sweden, Australia, and Singapore. By analyzing the music, visual references, and narrative structures of these memes, it highlights their role in evoking nostalgia for a glorified national past and framing the present as decadent. The findings reveal an emphasis on militarism, imperialism, and national identity, reinforced by reactionary slogans and disinformation targeting minorities. Thus, the LDA meme format acts as a political weapon, polarizing audiences through binary oppositions such as "us vs. them" and "glorious past vs. decaying present."